Urban development and financing of the municipalities. The impact of urban income municipal budgets (2005 - 2013) (Ciudades, 2017)
Economic activity in Spain has suffered a strong decline in the last decade. The fall in economic activity, namely the building activity, has severely affected all economic sectors. Spanish cities, due to its funding model, have been directly affected in its income and expenditure budgets. The decline in revenue associated to urban development has frequently been considered responsible for the deterioration of municipal accounts.The purpose of this paper is to analyze the impact of the crisis of the urban development in Spain in the economic and financial situation of the municipalities. In order to achieve this goal, we analyzed what incomes are associated with urban development, its evolution and its impact on municipal budgets of income and expenses in the period 2005-2013.The analysis leads to the conclusion that, in general terms, the Spanish municipalities have been able to survive the crisis mainly by reducing their investments and by replacing revenues with other income.
Keywords: crisis; municipalities; urban planning; urban income; municipal activity; investments